Q Fever Pneumonia in Southwest Germany: Radiographic and Clinical Findings - Biecker, Andrea; Bitzer, Michael; Biecker, Erwin (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose Q fever is a worldwide zoonosis that causes clinical symptoms ranging from mild flu-like symptoms to severe pneumonia and/or hepatitis. This retrospective study was conducted to describe the radiographic and clinical signs in patients with acute Q fever pneumonia in Southwest Germany.Patients and Methods 40 patients with IgM-positive Q fever-related pneumonia who were treated in the years 2006 to 2016 in our hospital were retrospectively identified. Clinical and laboratory data were analyzed. Chest radiographs were reviewed by two radiologists and interpreted using a standardized protocol.Results Females and males were equally affected. The mean age was 44.9 ± 15.7 years. About half of the patients (45 %) acquired their infection in the second quarter of the year. The main complaints were fever, cough and dyspnea. While the white cell blood count was in the normal range in most of the patients, the CRP value was markedly elevated. Q fever-related hepatitis was found in 63 % of the patients. Air space opacification was the predominant radiographic sign and was found in 27 of the patients (82 %). The typical chest radiographic pattern was a single segmental opacity. However, multiple segmental opacities and patchy opacities were also found. Lobar opacities were found in only 2 (6 %) of the patients.Conclusion Unilobar, unilateral, segmental opacities are the key feature of Q fever pneumonia chest radiographs. Definitive radiographic differentiation from other community-acquired pneumonias is not possible, but Q fever pneumonia should be considered in middle-aged patients with segmental opacities living in an endemic area.Key points Citation Format
Keywords: Q fever; pneumonia; coxiella burnetii; lung infection